RETRACTED: The Impact of WebQuest-Based Sheltered Instruction on Improving Academic Writing Skills, Soft Skills, and Minimizing Writing Anxiety - Salem, Ashraf Atta Mohamed S. (Frontiers in Education, 2022)
The current study explores the impact of learning in a sheltered Internet environment "WebQuest" on improving the academic writing skills of EAP non-native English speakers. It also investigates the impact of using sheltered online instruction on improving the soft skills of EAP language learners. In addition, the study assesses the impact of sheltered online instruction on reducing the writing anxiety levels of those writers in the IELTS Test (Writing Task 1 and 2). To reach such an end, three groups of EAP learners were selected to participate in the study adopting three learning styles: sheltered online instruction, unsheltered online instruction (free Google search), and sheltered offline instruction. Instruments used included a sample of the IELTS writing test, Brookings Soft Skills Rating Card, and Second Language Writing Anxiety Inventory (SLWAI). Sequential exploratory mixed method was used as it consists of both quantitative and qualitative data analyses for elaborate explanation of results. Successive rounds of data analyses showed a lot of gains of EAP students in academic writing skills and the level of their soft skills. It is also revealed that EAP students are not as anxious and reluctant to write as before. In addition, analysis of students' responses on the semi-structured interview revealed that learning in sheltered Internet environments represents an interesting as well as motivating learning experience. Therefore, it is recommended to implement sheltered online instruction strategies, especially WebQuest, in language learning and to design sheltered Internet environments other than Webquest to improve the quality of the teaching process.